Processes governing seasonal and interannual change of the Antarctic sea-ice area - Kimura, Noriaki; Onomura, Tomoyuki; Kikuchi, Takashi (Journal of oceanography, 2023)
Seasonal and interannual variabilities of sea-ice area in the Southern Ocean were examined using daily sea-ice concentration and ice velocity products for 2003–2019, derived from Advanced Microwave Scanning Radiometer for EOS (AMSR-E) and AMSR2 data. This study quantified the contributions to changes in the sea-ice area due to sea-ice transport and local processes, including ice formation/melting and ice deformation. Regional differences in the processes of seasonal advance and retreat of sea ice were elucidated. In most regions, sea-ice area increases mainly due to new ice formation in the marginal ice zone during autumn and winter. However, in the Amundsen–Bellingshausen seas, ice melting occurs in the marginal ice zone, even during winter, and expansion of the ice cover is attributable mainly to off-ice transport. With regard to interannual variability, the maximum ice area for each year is highly correlated with increase of ice area attributable to the ice formation in the marginal ice zone. Revealed processes that controls sea-ice changes could help improve our understanding of the sea-ice response to climate change.